2015
DOI: 10.21071/az.v64i246.397
|View full text |Cite
|
Sign up to set email alerts
|

Análisis económico y de la producción del descerdado manual de la fibra de llamas (Lama glama) Chaku

Abstract: Con el objetivo de evaluar el efecto de las diferentes zonas del vellón de llama sobre el rendimiento al descerdado manual, así como para realizar una evaluación económica de dicho proceso, se esquilaron 15 llamas de tipo Chaku o lanudo (7 juveniles y 8 adultas, que corresponden a la primera esquila) de un Centro de Investigación ubicado en Huancavelica, Perú. Cada vellón fue extendido y dividido dos lados y en 7 zonas corporales. Posteriormente en el laboratorio, previo pesado de cada zona, las muestras fuero… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
3
0
11

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(14 citation statements)
references
References 12 publications
0
3
0
11
Order By: Relevance
“…Hand-dehairing has demonstrated its feasibility [27], although the process is only efficient with double coated and intermediate coated fleece [28]. However, a recent work has shown that the per person and per hour yield is 9.9±1.1 g/person/h, which renders it economically unviable [29].…”
Section: Definition and Solution Of Prickle Effect Or Itchingmentioning
confidence: 99%
“…Hand-dehairing has demonstrated its feasibility [27], although the process is only efficient with double coated and intermediate coated fleece [28]. However, a recent work has shown that the per person and per hour yield is 9.9±1.1 g/person/h, which renders it economically unviable [29].…”
Section: Definition and Solution Of Prickle Effect Or Itchingmentioning
confidence: 99%
“…Hand-dehairing has demonstrated its feasibility [30], although the process is only efficient with double coated and intermediate coated fleece [31]. However, a recent work has shown that per person and per hour yield is 9.9±1.1 g/person/h, which renders it economically unviable [32].…”
Section: Definition and Solution Of Prickle Effect Or Itchingmentioning
confidence: 99%
“…La separación manual de fibra gruesa del vellón fino usualmente lo realizan las maestras descerdadoras (Sacchero y Mueller, 2005). Las cerdas se pueden orientar a la elaboración de alfombras, almohadas y sogas a nivel local, abriendo nuevas fuentes de empleo que generaría más ingresos económicos para las familias andinas (Quispe et al, 2015).…”
Section: Introductionunclassified